Climate change and the potential spread of Sorghum halepense in the central area of Argentina based on growth, biomass allocation and eco-physiological traits - Leguizamón, Eduardo Sixto (2014)
Despite the research dedicated to understand the potential climate change impacts on cropping systems, little attention has been given to potential effects on the geographic range of agricultural weeds. This paper reviews some biological and eco-physiological features of Sorghum halepense populations and their current and potential spread in a central eco-region of Argentina. Above ground biomass accumulation of the weed shows very high accumulation rates, which in the case of rhizomes is boosted as the available resources in propagule increases. An increase in temperature by 15 % may increase the relative growth rate (RGR) by 50 % in a 20–90 days growth period. Not only biomass output but also biomass allocation is directly related to adaptation in changing environments. Populations adapted to limited water conditions are able to maintain a higher RGR under water restriction as compared to those adapted to more humid conditions. Regarding the temperature, climate models are coincident: a range of increase from 0.9 °C in the south to 1.4 °C in the north of Argentina is predicted for 2020–2040, as compared to the period 1961–1990. Concerning the rainfall, not yet a prediction but a real fact is the displacement of isohyets from east to south. The average frequency of the weed in the pool of fields recently surveyed in the central region was 37 %, which increased to 42 % in the field borders. We consider that this frequency is high, since all crop fields are managed with high technology level and herbicides have been applied not only during the crop cycles, but also in previous fallows. The high RGR and other physiological features of weed populations at low water availability, which is more frequent in the west of the surveyed region where the frontier of extensive crops have recently displaced, may explain higher frequencies found. Well-adapted S. halepense populations invading rainfed crops in this eco-region will likely to take advantage under the forthcoming forecasted climatic conditions. Since temperatures increase from east to west as shown in climograms, S. halepense populations will likely perform even better under the new climate conditions. Coupling the actual management to physiological traits, it is envisaged an increase of the weed frequency in the surveyed eco-regions.